Pre and post-operative cerebral circulation assessment in anterior circulation intracranial aneurysm clipping patients using CT perfusion scan - Ab. Ghani, Ailani (2015)
Introduction Intracranial aneurysm is an abnormal dilatation of blood vessel that may rupture causing intracranial bleed; commonly subarachnoid haemorrhage (SAH). It is associated with high morbidity and mortality commonly due to vasospasm. Fisher grade and Navarro score are among the grading used to predict vasospasm while WFNS grading is used to predict its outcome. Few new modifications of the existing grading are available to obtain a higher sensitivity and specificity to predict the development of vasospasm but still unsuccessful. Once an intracranial aneurysm ruptures, patient’s cerebral blood flow may be disturbed during the acute phase of aneurysm rupture resulting in some effect on the patient’s cerebral circulation and autoregulation hence their cerebral perfusion even prior to the onset of vasospasm. This may influence the outcome of these patients. CTP is a method to measure the cerebral perfusion status and the values can be compared pre and post-operatively. Objectives To determine the relationship between cerebral CTP parameters (CBF, CBV and MTT) with Fisher grade, WFNS grade, Navarro score and modified Rankin score in patients undergoing intracranial aneurysm clipping at 3 and 6 months post-operatively as well as to compare the pre and post-operative CTP parameters in all patients, those with and without hypertension and those with new post-operative infarct. Methods This is a retrospective collection of data obtained from the electronic database for patients undergoing microsurgical clipping of intracranial aneurysm between 1st Jan 2013 to 30th June 2014 in Hospital Sungai Buloh. A total of 30 patients were recruited in this study. Data collected include the patient’s demographic profile, Fisher, WFNS and Navarro score. Both pre and post-operative CTP parameters (CBF, CBV and MTT) are collected to obtain the mean value. The presence of infarcted areas pre and post-operatively are obtained from the CT brain radiology report based on the CT brain done on the day of admission and postoperative day 1. Modified Rankin scale is taken during patients’ follow-up visit in clinic at 3 and 6 months. Results 30 patients are recruited for this retrospective study, majority are males (56.7%) with mean age of 48.9 years old. 85.7% of patients have hypertension and the commonest location for intracranial aneurysm is ACOM aneurysm (56.7%). Most of our patients are WFNS I (33.3%), Fisher grade 3 (50.0%) and Navarro score 6 (20.0%). There is no significant correlation between the mean CBF, CBV and MTT with WFNS, Fisher and Navarro score. There is a significant inverse moderate correlation between pre-operative mean MTT and mRS at 3 months (r=-0.393, p<0.05). Similarly, there was a significant inverse moderate correlation between pre-operative mean CBV and infarct (r=-0.366, p<0.05), as well as between pre-operative mean CBF and infarct (r=-0.456, p<0.05). There is a significant inverse moderate correlation between post-operative mean MTT and mRS at 3 months (r=- 0.401, p<0.05). In contrast, there is a significant moderate correlation between post-operative mean CBF and mRS at 3 months (r=0.454, p<0.05). Similar significant moderate correlation was found between post-operative mean CBF and mRS at 6 months (r=0.559, p<0.05). Comparing between the pre and post-operative mean MTT and mean CBF, all our patients have increase post-operative mean MTT with combination of reduce post-operative mean CBF (p<0.001) including those without hypertension. In hypertensive patients, there is only significant increase in the mean MTT. Similar increase in post-operative mean MTT and decrease in post-operative CBF is found in both patients with and without new infarct in their post-operative CT brain. Conclusion The conclusion from this study is there is no correlation between CT perfusion parameters with the Fisher grade, WFNS grade and Navarro score. For mRS at 3 months, there is an inverse correlation between the pre-operative mean MTT and post-operative mean MTT. A positive correlation is appreciated between mRS both at 3 months as well at 6 months with post-operative mean CBF. In general, patients undergoing microsurgical intracranial aneurysm clipping are bound to have increased MTT and reduced CBF. Interestingly, patients with no post-operative CT brain infarct also have similar findings of prolonged MTT with low CBF; indicating the alteration of cerebral perfusion is present even prior surgical intervention.